Strengthening Indonesian Banking Industry to Comply with ASEAN Banking Integration Framework Concerning Reciprocity and Gap-Reduction Principles - Handayani, Tri; Abubakar, Lastuti; W, Supraba Sekarwati; Nurlinda, Ida (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2018)
AbstractIndonesia maintains the commitment to strengthen economic growth and to promote financial stability in the ASEAN region. However, the differences of the economic growth among the ASEAN members become an obstacle for the ASEAN Banking Integration Framework (ABIF). The ABIF promotes the gap-reduction to enhance the ASEAN membersâ capacity to get benefits from the integration framework. However, some countries make some exceptions for the ABIF agenda. One of the benefits of ABIF is that Indonesia Banks can have access to broader market. To get the access, Indonesia has to fulfill as Qualified ASEAN Banks (QABs). One of the criteria is sufficient capital of banks. QABs requires bilateral agreement between state parties and promote the reciprocity and gap reduction principles. For instance, according to a schedule of specific commitment for banking sector, Indonesia and Malaysia had launched commercial presence on July 2017. One of the Indonesian Bank that comply with the criteria of QABs is PT. Bank Mandiri (Persero). It has established a branch office in Malaysia by the end of 2017. Thus, it proves that the Indonesian banking industry is ready to compete in the ASEAN Market.AbstrakIndonesia berkomitmen untuk tetap memperkuat pertumbuhan ekonomi dan meningkatkan stabilitas keuangan di wilayah ASEAN. Namun demikian, perbedaan pertumbuhan ekonomi diantara Negara-negara anggota ASEAN menjadi hambatan terlaksananya ASEAN Banking Integration Framework (ABIF). ABIF pada dasarnya dibentuk dengan tujuan untuk mengurangi kesenjangan dan meningkatkan kapasitas Negara-negara anggota ASEAN sehingga mendapatkan manfaat dari ABIF, walaupun beberapa negara masih dikecualikan dari beberapa agenda yang disepakati dalam ABIF. Pelaksanaan ABIF didasarkan pada perjanjian bilateral. Berdasarkan schedule of specific commitment Indonesia dan Malaysia meluncurkan kegiatan komersial banking pada July 2017. Salah satu Bank dari Indonesia yang memenuhi kriteria QABs adalah PT. Bank Mandiri (Persero) dan akan mengoperasikan kantor cabang penuh di Malaysia pada akhir 2017. Dengan demikian, merupakan suatu bukti bahwa industri perbankan Indonesia sudah siap menghadapi persaingan di Pasar ASEAN.Â DOI: https://doi.org/10.22304/pjih.v5n2.a5Â